Which of the following is a correct factorization of this trinomial?
-4x² +11x-6
A. -(4x+3)(x + 2). B. -4(x+3)(x + 2)
C. -(x+3)(x-4)
D. (-4x+3)(x-2)

Respuesta :

Answer:

D

Step-by-step explanation:

Step 1: Find the factors of 4 and -6

-4x² +11x-6

-4x           3  

1x           -2

(This works because -4 x -2 multiple to 8 and 3 x 1 gives you 3 and when you add it up it gives you the 'b' term)

Step 2: Read the numbers from left to right starting from the top to bottom

(-4x+3)(1x-2)

Therefore the answer to the question is D.

Answer:

A

explain

= -4x^2-11x-6

= -4x^2-8x-3x-6

= -4x(x+2)-3(x+2)

= (x+2) (-4x-3)

= -(4x+3) (x+2)